PENERAPAN PRINSIP-PRINSIP SYARIAH PADA PERJANJIAN ASURANSI SYARIAH DI RO TAKAFUL KELUARGA PEKALONGAN - Kuat Ismanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
Every economic and finance institution which operates based on shariah principles have to apply the Islamic syariah values. This provision has been set by the government, either by means of act or other regulations. The further technical provision is made by Dewan Syariah Nasional- Majelis Ulama Indonesia (the National Shariah Council-Indonesia Ulama Assembly) as the guidance in the fieldwork. Asuransi Takaful Keluarga (Family Takaful Assurance) is one of assurance sectors that its operational is based on the shariah principles. The result of a study showed that the contractapplicationthat is done has fulfilled the principles and prerequirements of syariah contracts. The model of contract that is operated is standard contract by considering the syariah aspects. In addition, it also attends to the contract principles such as permition, usefulness, justice, and other principles. Not only that, the done contract also has attended as maximal as possible to the syariah business ethics, by avoiding the syariah prohibitions such as gambling, deception, and unclearness in the contracts.